2003
DOI: 10.1161/01.str.0000086754.32238.da
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Viral and Bacterial Burden on Cognitive Impairment in Elderly Persons With Cardiovascular Diseases

Abstract: Background and Purpose-Inflammation and infectious etiology have been implicated in the pathogenesis of dementia.We sought to investigate whether the seropositivity of common infections was associated with cognitive function. Methods-Viral burden (seropositivity for herpes simplex virus type 1 [HSV-1], herpes simplex virus type 2 [HSV-2], or cytomegalovirus [CMV]) and bacterial burden (Chlamydia pneumoniae and Mycoplasma pneumoniae) were related to cognitive status and its impairment among 383 home-dwelling el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 30 publications
(24 reference statements)
7
95
0
1
Order By: Relevance
“…Many, but not all epidemiological studies, have documented the association of CMV seropositivity, atherosclerosis, and low cognitive function. In 383 homedwelling elderly with cardiovascular disease (mean age of 80 years), cumulative seropositivities of CMV and herpes simplex virus (HSV) 1 and 2 were associated with faster rate of cognitive decline over the 1-year follow-up based on MMSE measurements and clinical dementia rating (Strandberg et al 2003). In 1204 subjects aged 60-101 years (mean age of 70.3 years) of the Sacramento Area Latino Study on Aging (SALSA), high CMV antibody levels were associated with faster rate of cognitive decline over the 4-year follow-up (Aiello et al 2006) as well as with all-cause and cardiovascular mortality (Roberts et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many, but not all epidemiological studies, have documented the association of CMV seropositivity, atherosclerosis, and low cognitive function. In 383 homedwelling elderly with cardiovascular disease (mean age of 80 years), cumulative seropositivities of CMV and herpes simplex virus (HSV) 1 and 2 were associated with faster rate of cognitive decline over the 1-year follow-up based on MMSE measurements and clinical dementia rating (Strandberg et al 2003). In 1204 subjects aged 60-101 years (mean age of 70.3 years) of the Sacramento Area Latino Study on Aging (SALSA), high CMV antibody levels were associated with faster rate of cognitive decline over the 4-year follow-up (Aiello et al 2006) as well as with all-cause and cardiovascular mortality (Roberts et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, emerging epidemiological evidence suggests that inflammation triggered by viral infections such as cytomegalovirus (CMV) is a potent risk factor for not only atherosclerosis but vascular dementia and Alzheimer's disease in old age (Katan et al 2013;Strandberg et al 2003). Given a greater risk of agerelated deterioration of immune system, the effect of latent CMV infection on atherogenic and neurodegenerative process might be enhanced at advanced ages as compared to traditional vascular risk factors.…”
mentioning
confidence: 99%
“…In a prospective cohort of healthy individuals, Katan et al found a correlation between infectious burden and cognitive impairment assessed using the mini-mental state examination (MMSE) (Katan et al, 2013). Strandberg et al found that individuals with seropositive for some common viruses displayed cognitive impairment in home-dwelling elderly persons (Strandberg et al, 2003).…”
Section: Microbial Infection and Admentioning
confidence: 99%
“…e1a, there was a higher percentage of PD patients in the five-six seropositivities category (35% vs. 15%), a lower percentage in both the zero-two (61% vs. 74%) and three-four (4% vs. 11%) seropositivities than normal controls (P < 0.001). IB next was classified into viral burden and bacterial burden according to the previously published studies [11,16]. As only a few subjects had zero (11.8%) or three (4.4%) seropositivities toward B. burgodorferi, C. pneumoniae and H. pylori, bacterial burden was divided into two categories (zero-one and two-three).…”
Section: Exposure To Infectious Pathogens In Normal Controls and Pd Pmentioning
confidence: 99%